Finitude Rediscovered - Barber, Michael Patrick (Philosophy & theology, 1990)
According to Alfred Schutz’s theory of signification, based as it is on Husserl’s theory of appresentation, through marks and indications we overcome the small transcendences of space and time, through signs the medium transcendences of the Other’s difference from us, and through symbols the great transcendences of other finite provinces of meaning. This paper examines the implicat ions of the correlations between these transcendences and significations, and argues that Schutz’s order of significations reveals the profound irony that the more signifier-users seek to tame and subdue transcendences through significations, the more they discover how transcendences escape their dominion.